IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK DI KELAS V SEKOLAH DASAR - Dianti, Seruni; Kartono, Kartono; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aimed to describe implementation of thematic learning with a scientific approach in class V of Sekolah Dasar Negeri 14 Pontianak Selatan. The research method was descriptive research in the form of qualitative data. The data source of this research was the teacher and 24 students of Class V. Data collection techniques were observation, interviews, and documentation. Data analysis used steps of reduction data, presentation data, and drawing conclusions. Data collection instruments used were learning planning observation sheets and learning implementation observation sheets. This observation was made four times, the results showed that the teacher has made a thematic learning plan that used a scientific approach by studying the syllabus, identifying learning material, setting goals, developing learning activities that reflect the scientific approach (observing, asking, trying, reasoning, and communicating), elaborating the type of assessment, determining the allocation of time, and determining the learning resources. The teacher has carried out thematic learning with a scientific approach which includes activities namely: observing, asking, trying / collecting information, reasoning / processing information, and communicating. The obstacles experienced by teachers in applying thematic learning with a scientific approach inclueds obstacles in planning and implementing thematic learning with a scientific approach.Keywords: Implementation, Scietific Approach, Thematic Learning